Integration of FDM and vapor smoothing process: Analyzing properties of fabricated ABS replicas. (2018) - Kalyan, Kamal; Singh, Jaspreet; Phull, Gurpreet Singh; Soni, Sahil; Singh, Harpinder; Kaur, Gurpreet
Abstract: Fused deposition modelling (FDM) technique occupied a key position in additive manufacturing (AM) processes for the fabrication of functional and non-functional industrial parts. However, surface texture generated due to the fundamental working principle (layered manufacturing) and dimensional inaccuracy of fabricated parts, limits its domain particularly in precision industrial applications. In this research work, initially FDM based acrylonitrile butadiene styrene (ABS) replicas have been fabricated by varying the selected FDM parameters and their effect on the surface finish, shore hardness and dimensional accuracy has been determined as a pre-processing stage. In the post-processing stage, the exposure of hot vapors of acetone has been applied to the same fabricated replicas and the changes occurred in the surface finish, shore hardness and dimensional accuracy have been investigated. The study highlighted that post-processing of ABS replicas with hot vapors of acetone resulted in dramatic improvement of surface finish and shore hardness with negligible variations in part dimensions. Finally, parameter setting that gives acceptable results while considering all the responses simultaneously have been obtained using Minitab software..